Production and deployment of professional nurses in three nursing schools from 2005-2010: Towards strategic change in the Western Cape - Jooste, K (South African Journal of Higher Education, 2016)
The Department of Health of the Provincial Government of the Western Cape, in its Provincial Nursing Strategy of 2009, identified a shortage of nurses as a critical factor in its implementation. However, the increased student enrolment of the Western Cape Province continued without any research-based evidence about the deployment of nurses for service delivery. This paper describes the production and deployment of professional nurses at the Western Cape public health facilities for the period 2005 to 2010. A quantitative approach using an exploratory descriptive design was used during three research phases. The findings indicate that professional nurses produced with the four-year degree / diploma play an insignificant role in meeting the need for professional nurses in the Western Cape. From the findings, strategic direction is provided and described to policy makers about staffing professional nurses at the Western Cape public health facilities.